Effectiveness of Concentration of Liquid Organic Fertilizer from Rabbit Urine and Dosage of Rabbit Manure on the Growth and Yield of Red Lettuce (Lactuca Striva L.) - Bayu Adam Awali; M. Abror (Demeter: Journal of Farming and Agriculture, 2025)
This study aims to assess the effectiveness of various concentrations of liquid organic fertilizer (POC) from rabbit urine and doses of rabbit manure on the growth and yield of red lettuce (Lactuca striva L.). The research was conducted in February–March 2024 in Tebel Barat Village, Gedangan District, Sidoarjo Regency. The research design used was a Randomized Block Design (RBD) with two treatment factors. The first factor was the concentration of rabbit urine POC, which consisted of three levels, namely 20 ml/l water, 40 ml/l water, and 60 ml/l water. The second factor was the dose of rabbit manure fertilizer with three levels, namely 1.5 tons/ha, 3 tons/ha, and 4.5 tons/ha. Each treatment combination was repeated three times, resulting in 27 experimental plots. Data analysis was performed using analysis of variance (ANOVA) and followed by BNJ test. The variables observed included the number of leaves, plant height, root length, wet weight, dry weight, and harvest index. The results showed an interaction between treatments, with the best results obtained from the combination of 60 ml/l rabbit urine POC and 3 tons/ha manure for the variables of number of leaves, fresh weight, and dry weight. For the plant height variable, the highest results were obtained from the rabbit urine POC treatment at 60 ml/l water, while the manure fertilizer dose treatment showed no significant difference. As for the root length and harvest index variables, the treatments did not show any significant differences.